Surrogate Molecular Classification of Invasive Breast Carcinoma: A Comparison Between Core Needle Biopsy and Surgical Excision, With and Without Neoadjuvant Therapy. Issue 7 (August 2020) - Ambrosini-Spaltro, Andrea; Zunarelli, Elena; Bettelli, Stefania; Lupi, Massimo; Bernardelli, Giuditta; Milani, Marina; Ficarra, Guido
Abstract : Surrogate molecular classification identifies different subtypes of invasive breast carcinoma on the basis of their immunohistochemical markers. The purpose of the study is to verify whether the immunohistochemical markers and surrogate molecular subtypes can be correctly assessed on the core needle biopsy (CNB) when compared with the corresponding surgical excision (SE), with or without neoadjuvant treatment (NAT). Cases with invasive carcinomas identified on both CNB and SE were retrospectively selected. With immunohistochemistry for estrogen receptors (ER), progesterone receptors (PgR), Ki67, human epidermal growth factor receptor 2 (Her2), and molecular analysis for Her2, surrogate molecular classification was determined in 4 and 5 groups, according to the 2013 St Gallen consensus. A total of 1067 cases was considered and complete data for surrogate molecular classification were available for 988 cases (655 without NAT, 333 with NAT). Without NAT, concordance was strong for ER and Her2, moderate for PgR, and weak for Ki67; concordance for surrogate molecular classification was moderate. After NAT, lower concordance rates were recorded, with significant reduction of PgR ( P <0.001) and Ki67 ( P <0.001). Without NAT, the surrogate molecular subtypes of breast carcinoma can be reliably assessed on CNB; Ki67 and/or PgR may be repeated on SE when values are close to cutoffs to avoid tumor subtype misclassification. After NAT, it seems advisable to repeat at least Ki67 and PgR. Abstract : Supplemental Digital Content is available in the text.